Structural characterization of a polysaccharide from Certaria islandica and assessment of immunostimulatory activity - Utoomporn Surayot (2019)
© 2019 Elsevier Ltd In this study, Cetraria islandica polysaccharide (CIPs) was extracted by hot water extraction method and its effect on structural modification of immunomodulatory activities was investigated. This polysaccharide mainly consisted of carbohydrates (97.0%), Sulfate (1.2%) with one type of glucose. The average molecular weight (328.7 × 103 g/mol) was determined by size exclusion chromatography. The structure of the polysaccharide was found to be composed of (1→3) and (1→4)-β-D-glucopyranosyl units. The immunomodulatory activities of the crude polysaccharide and its derivatives, over-sulfated (OS1,2,3) and hydrolyzed (H1,2,3), were tested against NK-92 cells and RAW264.7 cells. The results obtained clearly demonstrated that over-sulfated (OS1,2,3)-treated NK-92 cells induced cytotoxicity in HeLa cells through the expressions of IFN-γ, NKp44, NKp30, and FasL. On the other hand, the hydrolyzed derivatives (H1,2,3) activated RAW264.7 cells through production of nitric oxide (NO) and mRNA expression of iNOS, IL-1, TNF-α, IL-6, IL-10 and IL-12 through the nuclear factor kappa-B (NF-κB) and mitogen activated protein kinases (MAPK) pathways. Our findings suggest that the presence of sulfate in the polysaccharide played a pivotal role in NK-92 cell however the Mw was a determinant factor in RAW264.7 cell activation, in which both cells were activated through the CR3 and TLR-4 signaling pathways.